Analisis Penerapan Hukum Tindak Pidana Pencemaran Nama Baik dalam Pasal 311 Ayat 1 Kitab Undang-Undang Hukum Pidana pada Pengadilan Negeri Kelas II Pasarwajo - Hayun, Hayun; Hasri, Hasirudin; Kahar, Amrun; Hezradian, Rahma Fathan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Different opinions are often the reason someone defames their honor and good name. This happens because of a low level of awareness of maintaining a tarnished good name through legal action. This research aims to legally review the application of article 311 paragraph (1) of the Criminal Code and the basis for the judge's consideration in handing down a decision against the perpetrator of the criminal act of defamation at the trial of case Number 37/PID.b/2012 PN PW Class II District Court Pasarwajo . This research is qualitative in form using a normative and empirical juridical approach which is focused on examining the application of legal rules according to the results of research in the field. Data collection techniques were carried out by direct research, conducting searches and reviewing library materials. The results and conclusions explain that the application of article 311 paragraph (1) of the Criminal Code concerning defamation in the trial of case Number 37/PID.b/2012 PN PW Class 11 District Court Pasarwajo is in this criminal case, the Defendant is named La Rubama Oka Bin H was tried because he had defamed his good name by slandering the victim named La Saheru Bin H. Zainuddin and the basis for the judge's consideration was the legal fact that the defendant La Rubama Oka Bin H. Umar defamed the victim La Saheru Bin H. could not prove his accusation.